Lung Recruitment Can Improve Oxygenation in Patients Ventilated in Continuous Positive Airway Pressure/Pressure Support Mode - Lovas, András; Németh, Márton Ferenc; Trásy, Domonkos; Molnár, Zsolt (Frontiers in Medicine, 2015)
Background: Recruitment maneuvers are often used in critical care patients with hypoxemic respiratory failure. Although continuous positive airway pressure/pressure support (CPAP/PS) ventilation is a frequently used approach, but whether lung recruitment also improves oxygenation in spontaneously breathing patients has not been investigated yet. The primary objective was to analyse the effect of recruitment maneuver on oxygenation in patients ventilated in CPAP/PS mode. Methods: Following baseline measurements PEEP was increased by 5 cmH2O. Recruitment maneuver was applied for 40 seconds with 40 cmH2O of PS. Measurements of the difference in PaO2/FiO2 and airway parameters measured by the ventilator were recorded immediately after recruitment then 15 and 30 minutes later. Thirty patients ventilated in CPAP/PS mode with a PEEP ≥ 5 cmH2O were enrolled in this prospective, observational study if their PaO2/FiO2 ratio was < 300 mmHg or required an FiO2 > 0.5. Results: Following recruitment maneuver patients were considered as non-responders (NR, n=15) if difference of PaO2/FiO2 < 20 % and responders (R, n=15) if difference of PaO2/FiO2 ≥ 20 %. In the NR-group PaO2/FiO2 decreased non-significantly from baseline: median [interquartile], PaO2/FiO2 = 176 [120-186] vs. after recruitment: 169 [121-182] mmHg, P = .307 while in the R-group there was significant improvement: 139 [117-164] vs. 230 [211-323] mmHg, P = .01. At the same time points dead space to tidal volume ratio (Vds/Vte) significantly increased in the NR-group Vds/Vte = 32 [27-37] vs. 36 [25-42] %, P = .013 but no significant change was observed in the R-group: 26 [22-34] vs. 27 [24-33] %, p = .386. Conclusion: Recruitment maneuver improved PaO2/FiO2 ratio by ≥ 20 % in 50 % of patients ventilated in CPAP/PS mode.